(untitled) (Journal of Parents and Teachers, 2014)
Bullying is still an alarming social issue and concern for schools. This article explains the different types of bullying, the typical profile of a bully, a victim and an observer. In addition it suggests some activities to work with bullying and humiliation in class. Prevention is the best antidote to fight against it.